2013
DOI: 10.1099/jmm.0.050013-0
|View full text |Cite
|
Sign up to set email alerts
|

Extended-spectrum β-lactamase/AmpC-producing uropathogenic Escherichia coli from HIV patients: do they have a low virulence score?

Abstract: Extended-spectrum b-lactamase (ESBL) production and quinolone resistance are often associated in enterobacteria. Prior exposure to 3G cephalosporins/quinolones accelerates the risk of resistance to both these groups of antibiotics. Hence, information on the antimicrobial resistance pattern of uropathogenic Escherichia coli (UPEC) isolates is important to better formulate the guidelines for the empirical therapy of urinary tract infection in the context of HIV/ AIDS. The aim of this study was to determine the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 53 publications
3
10
0
Order By: Relevance
“…85,86 The mass of the peptide expressed in yeast was consistent with the predicted mass based on the amino acid sequence, and not with the reported mass of 3340 Da. While E 50-52 produced in yeast was antimicrobially active against Gram-positive bacteria such as L. monocytogenes, it was not active against Gramnegative bacteria including C. jejuni.…”
Section: E 50-52supporting
confidence: 53%
See 1 more Smart Citation
“…85,86 The mass of the peptide expressed in yeast was consistent with the predicted mass based on the amino acid sequence, and not with the reported mass of 3340 Da. While E 50-52 produced in yeast was antimicrobially active against Gram-positive bacteria such as L. monocytogenes, it was not active against Gramnegative bacteria including C. jejuni.…”
Section: E 50-52supporting
confidence: 53%
“…85 E 50-52 expressed as a fusion protein in E. coli was reported to be active, following cleavage, against the Gram-negative E. coli as well as Gram-positive S. aureus and L. monocytogenes. 86 However, no testing against C. jejuni was reported. Whether or not this indicates that similar post-translational modifications may occur in E. coli and E. faecium is unclear.…”
Section: E 50-52mentioning
confidence: 99%
“…One study found that HIV-infected individuals with uropathogenic E coli were more likely to have ESBL and AmpC coproducers than non-HIV-infected individuals (71.1% vs 35.7%), although ESBL producers (without AmpC) were more common among non-HIV-infected individuals (16.7% vs 3.9%). 116 In a South African study, 13 of 25 HIVinfected children with Enterobacteriaceae causing bacteremia were found to be infected with ESBL isolates. 103 In the same study, nasopharyngeal colonization was investigated and found that of the 32 children with nasal colonization by Enterobacteriaceae, 16 (50%) were ESBL isolates.…”
Section: Dumford III and Skalweitmentioning
confidence: 98%
“…Another study investigating ESBL uropathogens found that fluoroquinolone resistance occurred in 77.6% of isolates from HIV-infected individuals versus 26.2% non-HIVinfected individuals. 116 Data on ESBL pathogens among HIV-infected individuals is also sparse, but the limited data do show ESBL pathogens to be common in this population. One study found that HIV-infected individuals with uropathogenic E coli were more likely to have ESBL and AmpC coproducers than non-HIV-infected individuals (71.1% vs 35.7%), although ESBL producers (without AmpC) were more common among non-HIV-infected individuals (16.7% vs 3.9%).…”
Section: Dumford III and Skalweitmentioning
confidence: 98%
“…At our institution, patients # 18 years of age are treated in the pediatric ED. The following patients were excluded: those who had a known urologic abnormality or comorbidity, those with an indwelling Foley catheter or who had a catheter removed within the previous 14 days, anyone with a history of kidney stones, those with diabetes mellitus, those who did not speak English, those who had received TMP-SMX prophylaxis within the previous 6 months, anyone with the human immunodeficiency virus (HIV) with no CD4 count on file or a CD4 count < 350 cells/mm 3 , those who had been transferred from another health care facility, and those who were pregnant (8). Pregnant women were excluded, as these patients are considered to have complicated infections according to the IDSA guidelines (1) .…”
Section: Participantsmentioning
confidence: 99%